Fighting Inflation Through Lowering of Monopoly Rents - Franz Nauschnigg (Wirtschaftsdienst)
Abstract High current inflation is driven in part by the monopoly rents of big companies. We do not have wage-price, but profit-price spirals. These were made possible by the creation, mostly through mergers and acquisitions, of market dominating firms. Fighting supply driven inflation through higher interest rates is not very efficient; it would be better to lower inflation by lowering the monopoly rents of companies like Gazprom. Energy price inflation could be lowered by regulators through lower monopoly rents for electricity and gas networks. The ASFINAG model offers a better financing alternative for these networks.